PESCA: a peer‐to‐peer social network architecture with privacy‐enabled social communication and data availability. Issue 1 (1st January 2015) - Raji, Fatemeh; Davarpanah Jazi, Mohammad; Miri, Ali
Abstract : The major challenge in current online social networks (OSNs) is privacy violation by OSN providers or unauthorised users. OSN providers collect unprecedented amounts of personal information for targeted advertising. Moreover, users are not able to share their social data with their friends with complete access control. Peer‐to‐peer (P2P) infrastructure is an interesting solution for a big‐brother‐free alternative to current OSN designs. However, the fundamental nature of P2P systems has dynamic peer turn‐over which results in data unavailability. Additionally, users' data must be available in the OSN when authorised data audiences want to access them. For these reasons, we propose a P2P‐OSN architecture which is composed of a privacy enabled setup for users' social communications and an adaptive replica placement strategy for ensuring availability for users' shared data. The proposed framework correlates the availability of shared content in the P2P‐OSN to the access control assigned to them. Our evaluations show the proposed P2P‐OSN has considerable improvements in providing data privacy and availability compared with the existing approaches.